Pathogen-derived resistance to dengue type 2 virus in mosquito cells by expression of the premembrane coding region of the viral genome. - Gaines, P J (1996)
The full-length premembrane (prM) coding region of the dengue virus type 2 (DEN-2; Jamaica) genome was expressed in C6/36 (Aedes albopictus) cells in either the sense or the antisense orientation from a double subgenomic Sindbis (dsSIN) virus. Northern (RNA) blot analysis confirmed the expression of sense or antisense DEN-2 prM RNA in infected C6/36 cells. PrM protein was demonstrated in cells infected with dsSIN virus expressing DEN-2 sense RNAs by an immunofluorescence assay. C6/36 cells were infected with each dsSIN virus at a multiplicity of infection (MOI) of 50 and challenged 48 h later with DEN-2 virus at an MOI of 0.1. Whereas C6/36 cells infected with a control of dsSIN virus supported high levels of DEN-2 replication, C6/36 cells infected with the dsSIN virus expressing prM antisense RNA were completely resistant to DEN-2 challenge. Cells expressing prM protein or untranslatable prM sense RNA also were resistant to DEN-2 challenge. Cells expressing prM protein demonstrated some breakthrough of DEN-2 virus when challenged at an MOI of 10. However, expressed untranslatable sense prM RNA conferred complete protection to challenge at the high MOI.